Paranita, a new genus of spiders from northeastern Argentina (Araneae, Trachelidae): Original images at full resolution - Ramirez, Martin Javier (2023)
For scanning electron microscope images (SEM) the samples were gradually dehydrated to 100% ethanol, critical point dried and coated with gold-palladium, and examined in a FEI-XL30 under high vacuum, with accelerating voltages 10–20 kV, using a secondary electron (SE) detector. Female genitalia were examined after clarification in clove oil and drawn with a camera lucida using an Olympus BH2 compound microscope. Incident light images were taken with a Leica M165C stereomicroscope, equipped with a Leica DFC290 digital camera.